Outcome and predictors of surgical repair of obstetric vesicovaginal fistula in a teaching hospital in ethiopia: retrospective cohort study - Amenu, Demisew; Workineh, Ahadu; Hika, Desta (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To determine outcomes of obstetric fistula repair and predictors of outcomes among patients with obstetric vesicovaginal fistula. Methods: A Hospital based Retrospective Cohort study design was conducted on all patients with Obstetric vesicovaginal Fistula, who were admitted to Gynecology ward, and had surgical repair from January 2011 to December 2014. Data was collected from patients’ chart, operation logbook and discharge logbook which were filled up from the entry of the patient to the hospital till her discharge. At discharge, a dye test was done to determine the outcome of repair. Results: 168 patients with obstetric vesicovaginal fistula were repaired during the study period. The age of the women ranged from 12 to 45 years with mean of 25 (± 6) years. Eighty percent of patients were laboring for two or more days, 46.4% delivered abdominally, and 85.7% ended up in stillbirth. Out of 93.4% patients who had successful closure of their fistula, 84.5% of patients had their fistula healed and continent, 8.9 % of them developed urinary incontinence while 6.5% of fistula repair had failed at the time of discharge. Unsuccessful fistula repair was significantly associated with being divorced/widowed (AOR 2.65 95%CI 1.06,6.67), Moderate/severe vaginal scaring (AOR5.25 95% CI 2.19, 12.60). Conclusions: In this study most fistula patients are older than 18 years, referred from health centers either for cephalopelvic disproportion or obstructed labor after prolonged labor at home, high success rates were achieved with surgical repair, and being divorced /widowed and marked vaginal scarring are predictors for unsuccessful fistula repair. Therefore, increasing access to comprehensive emergency obstetric and new born care is essential to minimize the delay contributing to perinatal mortality and obstetric fistula.